ANALYSIS OF CONSUMER PERCEPTION FACTORS THAT INFLUENCE THE CHOICE OF WOLFGANG PUCK RESTAURANT AT I GUSTI NGURAH RAI INTERNATIONAL AIRPORT - Wirasti, Norma; Kaihatu, Thomas Stefanus (International Journal of Review Management Business and Entrepreneurship (RMBE), 2024)
This research aims to analyze in depth the consumer perception factors that influence the choice of Wolfgang Puck Restaurant at I Gusti Ngurah Rai International Airport. The population in this research is Wolfgang Puck consumers. The sampling technique used in this research was a purposive sampling technique with a sample size of 100 respondents. The primary data used in this research was obtained through a questionnaire. The research model is confirmatory factor analysis. The results of the research were that five new factors were formed, namely hope factors, attention factors, product and atmosphere factors, stimulus factors, and lifestyle factors. The first factor includes good quality, product excellence, and information. The second factor includes behavior, needs, and goals. The third factor includes product attributes, product suitability, and the environment. The fourth factor includes trust, encouragement. The fifth factor includes encouragement from within, social encouragement, and satisfaction. These five factors represent 81.33% of the 15 elements studied. It is known that the expectation factor is the dominating factor in influencing consumers in choosing Wolfgang puck.